Cross-country Emission Tax Effect of Mergers. - Fikru, Mahelet G.; Gautier, Luis (Sage, 2020)
Recent studies show that mergers among polluting firms could affect the regulatory landscape of the industry and trigger a policy change. Using a two-country model, this study examines the effect o f a merger size, a s measured by the number of merging firms, on the optimal emission tax of another country. We show that, if pollution damages are not too large, a decline in the size of a merger reduces production and profits in that country, which affords a larger tax in the other country due to smaller profit-shifting c oncerns. On the other hand, if pollution damages are extremely large, a reduction in the size of a merger in one country reduces production in that country, but it also reduces production and emissions in the other country. Thus, the latter can induce a smaller emission tax. The change in the emission tax in both scenarios is consistent with cooperative outcomes.
Política de acceso abierto tomada de: https://uk.sagepub.com/en-gb/eur/journal-author-archiving-policies-and-re-use
Keywords: Impuestos ambientales; Sociedades - Fusión; Contaminación - Reducción; Mergers and acquisitions; Transboundary pollution; Product differentiation; Cooperative emission tax; Non-cooperative emission tax